A Short Note in Quantum Continuity Equation - Subedi, Bishnu Hari; Rana, Tara Bahadur (Nepal Journal of Mathematical Sciences, 2024)
In this article, we present a view that the interpretation of quantum mechanics lacks unanimous approval among physicists. To show its inadequacy, we describe the well-known measurement problem and discuss two solutions: an orthodox solution and hidden variables. We provide a brief overview of Bohmian mechanics. We then derive the continuity equation for quantum mechanics and show that a realist interpretation of the quantum probability current ->j leads to the guiding equation for Bohmian mechanics.